(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to identify the psychometric characteristics of testing learning skills in light of 21st century science skills. The descriptive analytical curriculum was used to achieve real results to reveal the psychometric characteristics of testing learning skills in the light of 21st century skills in science education, and in order to achieve real results, 1,070 students were selected as a sample of students from the eighth grade in the Directorate of Education in the Province of Authority from the public and private sectors. Where the researchers built the study tool, which was to test the skills of learning and teaching in the subject of general science after reference to literature and previous theoretical and scientific studies that were interested in detecting the skills of the twenty-first century in science education, and after the application of the test the results were analyzed and the results showed that the study tool that was built and applied to the individuals of the sample has appropriate psychological measurement characteristics, while the results of the study showed the absence of statistically significant differences in all demographic variables as a gender variable of the study, as well as the lack of Statistically significant differences in overall and sub-skills, with the exception of the standards (dimensions) of communication and cooperation as a result of the change in the education sector in favour of the public sector.